A New Approach to Secure The Distributed Database by Using SQL Firewall - A., Fairuzullah; Noraziah, Ahmad; Wan Maseri, Wan Mohd (2015)
This paper present a new approach database security works in a similar manner organization need layers of security around their data, with each layer protecting a specific area. The current trend of security attack is targeting any valuable data stored in a database such as financial data and student mark, including data theft, data modification or replay and data disruption. To understand how the system works, the system setting and the weaknesses of Single Enterprise Database in Distributed Database. This paper is about the design and develop a new framework to secure database access, a framework based on packet and content filtering on IP address, port and SQL statement. And simulate the framework and design database security framework. We address how to build the outcome of this is to reduce the risk of data manipulation and reduce the impact of internal threat and malicious insiders. The result shows that the proposed method succeeded in meeting those aspects of information security.